Cumulative Incidence of West Nile Virus Infection, Continental United States, 1999–2016 - Shannon E. Ronca (Emerging Infectious Diseases, 2019)
Using reported case data from ArboNET and previous seroprevalence data stratified by age and sex, we conservatively estimate that ≈7 million persons in the United States have been infected with West Nile virus since its introduction in 1999. Our data support the need for public health interventions and improved surveillance.